2011
DOI: 10.1007/s10801-011-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

Adjacency preservers, symmetric matrices, and cores

Abstract: It is shown that the graph Γ n that has the set of all n × n symmetric matrices over a finite field as the vertex set, with two matrices being adjacent if and only if the rank of their difference equals one, is a core if n ≥ 3. Eigenvalues of the graph Γ n are calculated as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In [30] it was shown that the graph formed by hermitian matrices over a finite field is a core, so its endomorphisms are characterized by the fundamental theorem. Same type of a result was obtained for n × n symmetric matrices over a finite field if n ≥ 3, while in 2 × 2 case the graph possesses a complete core [32]. Recently it was proved that any (finite) distance transitive graph is either a core or it has a complete core [12], though it is mentioned that is often difficult to decide which of the two possibilities occurs.…”
Section: Introductionmentioning
confidence: 68%
“…In [30] it was shown that the graph formed by hermitian matrices over a finite field is a core, so its endomorphisms are characterized by the fundamental theorem. Same type of a result was obtained for n × n symmetric matrices over a finite field if n ≥ 3, while in 2 × 2 case the graph possesses a complete core [32]. Recently it was proved that any (finite) distance transitive graph is either a core or it has a complete core [12], though it is mentioned that is often difficult to decide which of the two possibilities occurs.…”
Section: Introductionmentioning
confidence: 68%
“…Thus, the fundamental theorem of geometry of F q m×n can be formulated in terms of graph endomorphisms on (F q m×n , ∼). In [16,17], the author characterized the graph endomorphisms on symmetric matrix graphs and hermitian matrix graphs over a finite field. In Section 3, we will characterize graph endomorphisms on matrix graphs using results in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…The proof was later shortened in the thesis [16] by applying [8,Theorem 4.1]. Analogous result for symmetric matrices over a finite field was obtained in [15]. Here the graph is a core, unless we consider 2 ⇥ 2 symmetric matrices in which case the core of a graph is complete.…”
Section: Introductionmentioning
confidence: 90%